The foundation of the CIA : Harry Truman, the Missouri Gang, and the origins of the Cold War - Schroeder, Richard E. (Columbia : University of Missouri Press, 2017)
"This highly accessible book provides new material and a fresh perspective on American National Intelligence practice, focusing on the first fifty years of the twentieth century, when the United States took on the responsibilities of a global superpower during the first years of the Cold War. Late to the art of intelligence, the United States during World War II created a new model of combining intelligence collection and analytic functions into a single organization--the OSS. At the end of the war, President Harry Truman and a small group of advisors developed a new, centralized agency directly subordinate to and responsible to the President, despite entrenched institutional resistance. Instrumental to the creation of the CIA was a group known colloquially as the "Missouri Gang," which included not only President Truman but equally determined fellow Missourians Clark Clifford, Sidney Souers, and Roscoe Hillenkoetter."--Jacket
American National Intelligence: from the Revolutionary Army to World War II -- America in World War II and the beginnings of central intelligence -- William J. Donovan and the Office of Strategic Services -- Harry Truman, Sidney Souers, and the next steps -- The CIA, Roscoe Hillenkoetter, and the Cold War.
Includes bibliographical references (pages 163-169) and index.
Print version record.
eBooks on EBSCOhost
Keywords: United States. -- Central Intelligence Agency -- History; Truman, Harry S., -- 1884-1972.; Truman, Harry S., -- 1884-1972; United States. -- Central Intelligence Agency; USA -- Central Intelligence Agency; Cold War; Intelligence service -- United States -- History -- 20th century; Guerre froide; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; Intelligence service; United States; 1900-1999; History; History; History